Análisis de la ejecución presupuestal del programa control y prevención en salud mental frente al Covid-19 en Loreto, periodo 2020 – 2021 - Torres Tapullima, Esther (2023)
In the present investigation, the budgetary execution for Control and Prevention in Mental Health against COVID-19, in Loreto, period 2021-2020, was analyzed through a descriptive and correlational study, with a quantitative approach, and non-experimental design. The study was carried out on a population made up of statistical data from a given period, obtained from historical information published by the Loreto Regional Health Management, the Ministry of Economy and Finance and the Ministry of Health, on the budget execution of the program. (Strategy in Mental Health). Documentary analysis or review was used as an exploration technique. Likewise, the Registration Form was used as an instrument. The level of execution of income and expenses in the health sector program, in the department of Loreto, in the years 2020 and 2021 (COVID-19 pandemic), found that its main financing was Ordinary Resources, and the Primary attention to the obligations in the different products and goals of the program were in current expenses (in goods and services, personnel, social obligations and other programmed expenses), with less attention being paid to "Acquisition of Non-Financial Assets".